Ergonomic risk and musculoskeletal disorders among food industry workers in Callao in 2021 - Torres-Ruiz, Sally (2023)
Objective: To determine the relationship between ergonomic risk and musculoskeletal disorders (MSDs) among food industry workers in Callao, 2021.Materials and methods: A quantitative, correlational, cross-sectional, non-experimental study. The sample consisted of 184 workers. The main variables were measured with the Rapid Entire Body Assessment (REBA) and the MSDs with Kuorinka’s Standardized Nordic questionnaires. A bivariate analysis of the primary and secondary variables was performed using the chi-square test, Pearson correlation coefficient and Student’s t-test. A significance level less than or equal to 0.05 was considered. Results: Out of all workers, 43.48 % had a low ergonomic risk and 79.89 % developed MSDs, with greater discomfort in the back, with 27.03 %, and the hand (right wrist), with 26.35 %. In addition, the relationship between the ergonomic risk factor and MSDs was significant (p = 0.001), with a positive correlation of 0.301. Likewise, MSDs were relatedto sex (p = 0.015), marital status (p = 0.011), type of contract (p = 0.001) and job position (p = 0.000).Conclusions: A relationship was found between ergonomic risk and MSDs among food industry workers in Callao, 2021. Moreover, most workers developed MSDs, with greater discomfort in the back. The variables of the present study should betaken into account when exploring effective and concrete intervention strategies to prevent MSDs. It is recommended to raise awareness of workers and employers about the appropriate ergonomic and personal measures necessary to improvethe safety and well-being of workers.